Study of Tumor Necrosis Factor-Alpha-Induced Protein 3 Gene Single-Nucleotide Variants in JAK2 V617F-Positive Myeloproliferative Disorders: A Case–Control Study - Abdelghany, Wafaa M.; El Husseiny, Noha M.; Fekry, Gehad H.; Korayem, Osama H.; Helmy, Rehab (Open Access Macedonian Journal of Medical Sciences, 2022)
Background and Objectives: Myeloproliferative neoplasms (MPNs) are Philadelphia negative disorders involving polycythemia vera (PV), essential thrombocythemia (ET), primary myelofibrosis (PMF). Although JAK2 mutation is almost involved, other several mutations are linked to MPNs risk and prognosis. TNFAIP3 genetic mutations are related to several cancers and autoimmune diseases. Our study aimed to demonstrate the effects of rs2230926_T/G & rs5029939_C/G SNVs of TNFAIP3 gene on the risk and prognosis of JAK2 V617F positive MPNs. Methods: Matched 2 groups in age, sex and race were enrolled in our research; 80 MPNs cases group and 130 normal healthy controls group with follow up of MPNs cases for 3 years. Taqman assay probes involved in real time polymerase chain reaction (PCR) were utilized for variants analysis. Results: The rs2230926 & rs5029939 SNVs were in modest linkage disequilibrium (LD) in MPNs cases. The observed frequencies of G allele and its genotypes of both variants were more prevalent in MPNs patients than normal controls. The bleeding symptoms and the presence of splenomegaly were more existent in the heterozygous genotype and the combined G involved genotypes respectively. The overall survival (OS) was lower in G containing genotypes of both variants but the progression free survival (PFS) was affected only in rs5029939 SNV. Conclusion: Our study revealed the association of G containing genotypes of both rs2230926 & rs5029939 SNVs to the increased MPNs incidence as well to poor clinical course and prognosis of JAK2 V617F positive MPNs disorders in Egyptian ethnic.